2018
DOI: 10.1007/s12035-018-1021-0
|View full text |Cite
|
Sign up to set email alerts
|

HERC1 Ubiquitin Ligase Is Required for Normal Axonal Myelination in the Peripheral Nervous System

Abstract: A missense mutation in HERC1 provokes loss of cerebellar Purkinje cells, tremor, and unstable gait in tambaleante (tbl) mice. Recently, we have shown that before cerebellar degeneration takes place, the tbl mouse suffers from a reduction in the number of vesicles available for release at the neuromuscular junction (NMJ). The aim of the present work was to study to which extent the alteration in HERC1 may affect other cells in the nervous system and how this may influence the motor dysfunction observed in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…(2) anomalous myelination of peripheral nerves and delayed action potential transmission 15 ; (3) increase of autophagy signs in projection neurons of central nervous system as the hippocampal CA3 pyramidal neurons, the neocortical pyramidal neurons, and the motor neurons of the spinal cord 13 ; and, (4) impairment of associative learning linked to absence of LTP and anomalous spinogenesis of the neurons of the lateral amygdala 14 . Therefore, as part of the ubiquitin-proteasome system (UPS) whose alterations have been related with several neurodegenerative diseases of nervous system [28][29][30][31][32][33][34] , all these findings have been explained as the effect of the dysregulation of the autophagy 5,[13][14][15] and/or of the mammalian target of rapamycin complex 1 (mTORC1) altered regulation 5,15 . Present results in hippocampal cultured neurons show that tbl presynaptic terminals possess a noticeable decrease in the number of presynaptic terminals relative to the control ones, which in addition display:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2) anomalous myelination of peripheral nerves and delayed action potential transmission 15 ; (3) increase of autophagy signs in projection neurons of central nervous system as the hippocampal CA3 pyramidal neurons, the neocortical pyramidal neurons, and the motor neurons of the spinal cord 13 ; and, (4) impairment of associative learning linked to absence of LTP and anomalous spinogenesis of the neurons of the lateral amygdala 14 . Therefore, as part of the ubiquitin-proteasome system (UPS) whose alterations have been related with several neurodegenerative diseases of nervous system [28][29][30][31][32][33][34] , all these findings have been explained as the effect of the dysregulation of the autophagy 5,[13][14][15] and/or of the mammalian target of rapamycin complex 1 (mTORC1) altered regulation 5,15 . Present results in hippocampal cultured neurons show that tbl presynaptic terminals possess a noticeable decrease in the number of presynaptic terminals relative to the control ones, which in addition display:…”
Section: Discussionmentioning
confidence: 99%
“…The animal model of HERC 1 mutation, the tambaleante mouse, was first described as an example of adult cerebellar ataxia by autophagy Purkinje cell death 5 , 9 12 . Later studies showed more neurodevelopmental damages to tbl mice phenotype as: (1) delay in synaptic development and maturation of NMJ 16 ; (2) anomalous myelination of peripheral nerves and delayed action potential transmission 15 ; (3) increase of autophagy signs in projection neurons of central nervous system as the hippocampal CA3 pyramidal neurons, the neocortical pyramidal neurons, and the motor neurons of the spinal cord 13 ; and, (4) impairment of associative learning linked to absence of LTP and anomalous spinogenesis of the neurons of the lateral amygdala 14 . Therefore, as part of the ubiquitin–proteasome system (UPS) whose alterations have been related with several neurodegenerative diseases of nervous system 28 34 , all these findings have been explained as the effect of the dysregulation of the autophagy 5 , 13 15 and/or of the mammalian target of rapamycin complex 1 (mTORC1) altered regulation 5 , 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herc1 Gly483Glu mutant mice, termed tambaleante , present with delayed growth, short body, high juvenile mortality, and severe ataxia, the latter due to Purkinje cell loss beyond the age of 2 months, correlating with autophagy and decreased mTOR signalling (Mashimo et al, 2009). Tambaleante mice have impaired neurotransmitter release in neuromuscular junctions (Bachiller et al, 2015), defective ubiquitin-proteasome-driven protein aggregate clearance, and increased autophagic flux in neocortical pyramidal, CA3 hippocampal pyramidal and spinal cord motor neurons (Ruiz et al, 2016) and poor myelinisation and delayed action potential transmission (Bachiller et al, 2018). Furthermore, they have impaired associative learning (Perez-Villegas et al, 2018).…”
Section: Physiological Implicationsmentioning
confidence: 99%